Germination, physiological and biochemical responses of acacia seedlings (Acacia raddiana and Acacia tortilis) to petroleum contaminated soils. (March 2018) - Tran, Thanh Hoai; Mayzlish Gati, Einav; Eshel, Amram; Winters, Gidon
Abstract: Along the arid Arava, southern Israel, acacia trees ( Acacia raddiana and Acacia tortilis ) are considered keystone species. Yet they are threatened by the ongoing aquifer depletion for agriculture, the conversion of natural land to agricultural land, seed infestation by bruchid beetles, and the reduction in precipitation level in the region. In the acacia dominated Evrona reserve (southern Arava), adding to these threats are recurrent oil spills from an underground pipeline. We report here a study of the effects of contaminated soils, from a recent (December 2014) and a much older (1975) oil spills. The effects of local petroleum oil-contaminated soils on germination and early growing stages of the two acacia species were studied by comparisons with uncontaminated (control) soils from the same sites. For both acacia species, germination was significantly reduced in the 2014 oil-contaminated soils, whereas delayed in the 1975 oil-contaminated soil. There was no significant effect of oil volatile compounds on seed germination. At 105 days post transplanting (DPT), height, leaf number, stem diameter, and root growth were significantly smaller in the oil-contaminated soils. While photosynthetic performance (quantum yield of photosystem II) did not differ considerably between treatments, reductions of chlorophylls content and protein content were found in seedlings growing in the contaminated soils. Significant increases in superoxide dismutase (SOD) and ascorbate peroxidase (APX) activities were found in roots of seedlings growing in oil-contaminated soils. These results demonstrate that seed germination and seedling growth of both acacia species were strongly restricted by oil contamination in soils, from both recent (2014) and a 40-year old (1975) oil spills. Such long-term effects of oil spills on local acacia seedlings could shift the structure of local acacia communities. These results should be taken into account by local authorities aiming to clean up and restore such polluted areas. Graphical abstract: Highlights: Acacia germination significantly reduced or delayed in the oil-contaminated soils. Oil-contaminated soils reduced both aboveground and belowground growth parameters. In roots, oil-contaminated soils increased activity of antioxidants (SOD, APX). Long-term effects of oil spills could shift structure of local acacia communities. Abstract : Long term effects of oil contaminated soils could shift the structure of local acacia communities.